2020
DOI: 10.3390/geosciences10020059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Zeolite as a Potential Reactive Medium in a Permeable Reactive Barrier (PRB): Batch and Column Studies

Abstract: The purpose of this work is to evaluate the capacity of a natural zeolite to be used as a reactive material in a permeable reactive barrier (PRB) to remove inorganic contaminants from groundwater. To this aim, zeolite samples were subjected to characterization tests, column experiments, batch tests and a flushing process to evaluate the adsorption and desorption capacities of the zeolite. In the column experiments, the samples were subjected to eight successive cycles involving the percolation of a potassium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Generally, the Si/Al ratio is theoretically related to the CEC value. Zeolites with lower Si/Al ratio have higher CEC values [ 28 ]. As it can be seen, the Si/Al of MZ S1 was 5.20 and its CEC value was 1.60 meq/q, while the Si/Al and CEC value of RZ S1 was 4.89 and 1.18 meq/q, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the Si/Al ratio is theoretically related to the CEC value. Zeolites with lower Si/Al ratio have higher CEC values [ 28 ]. As it can be seen, the Si/Al of MZ S1 was 5.20 and its CEC value was 1.60 meq/q, while the Si/Al and CEC value of RZ S1 was 4.89 and 1.18 meq/q, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the groundwater level and rockhead depth combined with the permeability, porosity, and storage capacity characteristics of geological material, units 1 and 2 had potential for a wide range of SuDS types, while unit 3 had a more restricted potential. Notably, the most favorable infiltration conditions were presented by unit 2, but this unit also had the greatest potential for groundwater contamination, and it is advisable to adopt systems that allow the use of horizontal permeable reactive barriers in accordance with the guidelines presented in [47,48]. Units 1 and 3 had water interfaces that could affect the efficiency of infiltration-based systems; these interfaces were higher in unit 3 than in unit 1.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, geological materials have high erodibility and low cohesion, which favors the instability of excavated slopes. It is recommended that the systems be implemented with protection measures, such as permeable reactive barriers, as proposed by [47,48]. Thus, the installation of systems with a lower runoff accumulation magnitude should be prioritized, as they allow better control of possible contaminants and the area affected by infiltration, in addition to reducing installation costs.…”
Section: Unitmentioning
confidence: 99%
“…The choice of solvents for desorption and regeneration tests was guided by the existing literature [34,35]. The aim of desorption with deionized water is to evaluate the ability of the adsorbent particles to release ions with the flow of a natural solvent, thereby preventing the introduction of a new element and consequently avoiding the contamination of the area with a new chemical product [36]. On the other hand, research has indicated that the use of HCl 0.1 N is the most effective eluent for regenerating these materials [37].…”
Section: Desorption and Regeneration Experimentsmentioning
confidence: 99%